Unmet challenges in septoplasty–nordic studies from a uniform healthcare and geographical area - Hellgren, J; Lundberg, M; Rubek, N; von Buchwald, C; Steinsvåg, S; Mäkitie, A (Frontiers in Surgery, 2022)
Purpose Nasal septoplasty is one of the most common surgical procedures in otorhinolaryngology and optimising both patient selection and the surgery is a challenge. The Nordic countries have similar public healthcare systems and comparable populations in terms of size. Methods This is a review of studies of outcome and predictors related to septoplasty from Denmark, Finland, Norway and Sweden, published during the last decade. The aim of this review was to identify areas in need of further research to meet the challenges of septoplasty in the Nordic countries with reference to international data. Results Postoperative patient satisfaction at 6–12 months was reported in around 2/3 of the patients and well in line with international data. Patients with more severe symptoms had a higher chance of improvement. Lack of standardisation in patient selection, surgical methods and skills, and follow up procedures, still makes it difficult to explain the 25% failure rate in septoplasty surgery. Conclusion This review of the Nordic studies from the last decade shows that septoplasty in general is effective in relieving nasal obstruction. There is a need for studies addressing the standardisation of diagnostic tools and algorithms and the systematic and continuous implementation of follow-up of the surgical results at both departmental and personal level. This includes an awareness of how surgical skills in septoplasty are obtained and maintained.